Possible virulence factors involved in bacteraemia caused by Aeromonas hydrophila - Vadivelu, J. (Microbiology Society, 1995)
Eighteen strains of Aeromonas hydrophila from patients with bacteraemia were investigated for possible virulence factors. Cytotoxin and haemolysin were produced by all strains, whereas cholera toxin-like factor was produced by 33% of strains only. Enterotoxin production was not detected. Haemagglutination of guinea-pig, fowl and rabbit erythrocytes was demonstrated by 83%, 67% and 61% of strains, respectively. Fucose- and mannose-sensitive haemagglutinins were predominant. None of the strains agglutinated sheep erythrocytes. Extrachromosomal DNA was detected in 17 strains, 16 of which had a plasmid (3.6-5.1 MDa), the majority being between 4.6 and 5.1 MDa.